PROFIL HORMON ESTROGEN DAN PROGESTERON INDUK SAPI SILANGAN SIMMENTAL-PERANAKAN ONGOLE DENGAN SUPLEMENTASI LEGUM SEBAGAI SUMBER FITOESTROGEN - M.W. Tiro, Batseba; Baliarti, Endang; Soetrisno, R. Djoko; Hartadi, Hari; Kustono, Kustono (FAPETKAN UNTAD, 2011)
This study aims to find out follicular development and hormone profiles post partum Simmental-Ongole cross cattle (SimPO) with legume phytoestrogen supplementation. Research was carried out since April to December 2010 at pens of Laboratory of Animal Production, Faculty of Animal Husbandry, Gadjah Mada University. A total of 15 SimPO post calving were used and distributed into three treatment groups, namely: PO treatment or control (only fed with the standard), PI : PO + 5 g phytoestrogen and PII: PO + 10 g phytoestrogen. Supplementation of phytoestrogen was derived from soy straw. The parameters were estrogen and progesterone profiles and follicle growth dynamic of post partum. The results of this study indicated that supplementation with 5 g phytoestrogen was more significant in affecting the increase in estrogen and progesterone concentrations, compared with the supplementation with 10 g phytoestrogen and control. Ovarian activity characterized by the development of follicles the SimPO began on day 4 post partum for all treatments but only PII treatments indicated that the development of follicles reached the de Graaf follicle with estrogen concentration of 17,801 pg/ml. Key words : Development, estrogen, follicle, legume, phytoestrogen, progesteron.